Monitoring Server Berbasis SNMP Menggunakan Cacti pada Server Lokal - Muhammad Yusuf Bagus Rasyiidin; Fachroni Arbi Murad (Jurnal Ilmiah FIFO, 2021)
Abstract - SNMP is a network protocol used for monitoring network devices, especially servers, which allows senders and recipients to exchange information. With SNMP all device activities can be monitored using several additions available on Linux operating systems namely apache, PHP, SNMP, MySQL, and Cacti. Server monitoring is needed to find and solve some problems on a network that has many devices, aiming to monitor all network devices using Cacti. A problem that often occurs on a network is a slow connection and disconnected, with the presence of Cacti a network administrator can identify problems and fix them.